Design and Balancing Load Current in 3-Phase System Using Microcontroller ATMEGA 2560 - Partha, Cok Gede Indra (International Journal of Engineering and Emerging Technology, 2017)
The design of balancing the load current on three-phase systems using a microcontroller ATMega 2560 is a tool that serves to reduce the power loss. Power loss due to the load current unbalance the current flows in the neutral phase on three-phase systems. Current flows in the neutral phase distribution transformer into a detriment to PT. PLN (Persero) for the power lost to the earth and can not be used by consumers. So that it will balanced the load current to reduce the value of neutral current. The tool is also equipped with a monitoring system that displays current magnitude of each phase including the neutral phase. The methods in making this tool is divided into two parts: first, the design of hardware consist of designing electronic components which are used by the current sensor circuits, relay, LCD (Liquid Crystal Display) etc. Second, the design of software is a tool listing program procedure including the monitoring program displays the current of each phase on LCD using the Arduino IDE. SCT013-030 current sensor used, the output of the current sensor is connected to the pin ADC (Analog to Digital Converter) microcontroller ATMega 2560. Then microcontroller process the data and generate a current value displayed on the LCD. The other result of processing current value is a command to enable or disable the relay that connects three-phase resource with single-phase loads. The result of the test design of balancing load current on three-phase system using a microcontroller ATMega 2560 succeed balancing the load current by moving the channel load of sequence number load the smallest connected to the phase with the current biggest load toward a phase that has a load current smallest when neutral current exceeds the limit is permitted. In this situation, the neutral current will not be possible be zero. In fact, the maximum current value for the neutral phase for PT. PLN (Persero) 50 amperes calibrated to 1 ampere and is used as a limit on this prototype. If the neutral current on LCD monitor exceeds 1 ampere, then there will be balancing of the load current. The current sensor measurement results are displayed on a monitoring approach measurement result using pliers ampere.